P‐195: Equivalent Lifetime Method to Improve OLED Luminance Degradation. Issue 1 (2nd June 2017) - Fan, Rui; Zhang, Xiaoning; Tu, Zhentao; Hwang, Taijun; Fu, JianHang; Lu, Poyen; Jou, Mingjong
Abstract : Equivalent lifetime method to estimate the luminance degradation degree and improve the lifetime of the OLEDs was proposed. The equivalent lifetime was calculated by converting the display time at different luminance with the same degradation degree with ascertained luminance decay curve. The calculation accuracy can reach 99.98% and lifetime can extend 13.3%.